Management of Educational Facilities and Infrastructure to Support the Quality of Learning (Multi-Site Study at SMK Krian 2 and SMK YPM 1 Taman Sidoarjo) - Elyus, Dinda Septiana; Sholeh, Muhammad; Khamidi, Amrozi (Journal of English Language and Education, 2025)
The management of educational facilities and infrastructure is a crucial factor in supporting the quality of learning, particularly at the vocational high school level (Sekolah Menengah Kejuruan/SMK), which emphasizes skills- and practice-based learning. This study aims to describe and analyze the management of educational facilities and infrastructure in supporting learning quality through a multi-site study at SMK Krian 2 and SMK YPM 1 Taman Sidoarjo. This research employed a qualitative approach with a multi-site study design. Data were collected through in-depth interviews, observations, and documentation studies. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that the management of facilities and infrastructure at SMK YPM 1 Taman has been implemented systematically, in a well-planned manner, and based on inventory data, enabling it to optimally support the quality of learning. Meanwhile, the management of facilities and infrastructure at SMK Krian 2 still faces challenges, particularly in data-based planning, scheduled maintenance, and the documentation of monitoring and evaluation activities. Cross-site findings reveal that careful planning, clear division of responsibilities, and continuous monitoring and evaluation are key factors for successful facilities and infrastructure management in improving the quality of learning at vocational high schools.